2005
DOI: 10.1136/ijgc-00009577-200501000-00026
|View full text |Cite
|
Sign up to set email alerts
|

A case of protrusion of an intraperitoneal chemotherapy catheter through rectum

Abstract: Bowel penetration of an intraperitoneal catheter occurred in a patient who had received a course of uncomplicated intraperitoneal chemotherapy for a persistent ovarian carcinoma. One month after the termination of chemotherapy, she presented with protrusion of a catheter through anus. At operation, the catheter was removed, the rectum was repaired primarily, and a cytoreductive surgery was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In our study, there were no complications related to bowel, though reported to occur at a rate of 3-5 % and include fistulas, catheter migration in to the bowel lumen, bowel obstruction and perforations [7][8][9][10][11][12]. In our study, none of the venous catheters had obstruction but in the initial 20 fenestrated catheters five had obstruction, indicating that venous catheters are less prone for obstruction.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In our study, there were no complications related to bowel, though reported to occur at a rate of 3-5 % and include fistulas, catheter migration in to the bowel lumen, bowel obstruction and perforations [7][8][9][10][11][12]. In our study, none of the venous catheters had obstruction but in the initial 20 fenestrated catheters five had obstruction, indicating that venous catheters are less prone for obstruction.…”
Section: Discussionmentioning
confidence: 48%
“…Potential benefits of adhesion barriers have not been validated in a randomized trial. IP catheters should be removed after completion of current therapy, as complication rates are high, on retaining for longer period [11]. It is removed under local anesthesia on outpatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis cannot draw conclusions on hematologic, renal, neurologic, and lung toxicity, as the data are too heterogeneous and will largely depend on the regimen used. The results of this meta-analysis should be used as part of this decision-making process, taking into consideration the potential for catheter-related complications that include blockade, leakage, infection, bowel perforation, and fistula formation (70,(74)(75)(76)(77) . The optimal dose, timing, and mechanism of administration of IP chemotherapy cannot be addressed from this metaanalysis (73) .…”
Section: Ip Chemotherapy As First-line Treatment In Patients With Minmentioning
confidence: 99%
“…In addition, if the catheter is fixed to the midline, it might get blocked by remnants of omental fat. Complications have been reported when the catheters are retained (21,22) . It is advisable to remove the catheter once treatment is completed.…”
Section: Catheter Optionsmentioning
confidence: 99%